2007
DOI: 10.1038/sj.bjp.0706987
|View full text |Cite
|
Sign up to set email alerts
|

Suberosin inhibits proliferation of human peripheral blood mononuclear cells through the modulation of the transcription factors NF‐AT and NF‐κB

Abstract: Background and purpose: Extracts of Plumbago zeylanica containing suberosin exhibit anti-inflammatory activity. We purified suberosin from such extracts and studied its effects on a set of key regulatory events in the proliferation of human peripheral blood mononuclear cells (PBMC) stimulated by phytohemagglutinin (PHA). Experimental approach: Proliferation of PBMC in culture was measured by uptake of 3 H-thymidine; production of cytokines and cyclins by Western blotting and RT-PCR. Transcription factors NF-AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 51 publications
1
39
0
Order By: Relevance
“…Previous studies have shown that a series of cytokines such as IL-2 and IFN-γ are important in the growth of antigen-or PHA-induced PBMCs (Robb, 1984;Young, 1996;Chen et al, 2007). PHA, a T lymphocyte mitogen, stimulates the proliferation of T cells by interacting with the N-acetylgalactosamine glycoproteins expressed on the cells (Janeway et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that a series of cytokines such as IL-2 and IFN-γ are important in the growth of antigen-or PHA-induced PBMCs (Robb, 1984;Young, 1996;Chen et al, 2007). PHA, a T lymphocyte mitogen, stimulates the proliferation of T cells by interacting with the N-acetylgalactosamine glycoproteins expressed on the cells (Janeway et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity of piperine on PHA-stimulated PBMCs was studied using microscopic examination to ensure that the inhibitory action of piperine was due to direct cytotoxicity. In addition, it has been previously verified by many researchers that a series of cytokines such as interleukin-2 (IL-2) and interferon-γ (IFN-γ) are important for the growth of PBMCs induced by antigens or PHA (Robb, 1984;Young, 1996;Chen et al, 2007). Therefore, the production and gene expression of both cytokines were examined in this study.…”
Section: Introductionmentioning
confidence: 99%
“…RT-PCR was carried out according to a previously described method [15]. Briefly, RNA (1 μg) was reversetranscribed to cDNA by the Advantage™ RT-for-PCR kit (Clontech, USA) according to the manufacturer's instructions.…”
Section: Reverse Transcription-polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%
“…To determine exactly how cucurbitacin R exerts these effects, we have to examine the principal event in the generation of the immune response, namely, the activation and clonal expansion of T lymphocytes. These are spontaneously arrested in the G 0 /G 1 phase and remain quiescent for long periods until they are exposed to specific agents (Chen et al, 2007). The activation of T cells with agents such as antigens or phytohemagglutinin A triggers the biochemical events that induce resting T cells to enter into the cell cycle after proliferation and differentiation (Kuo et al, 2003), during which the transcription factor NFAT is involved.…”
Section: Cucurbitacin R Inhibits Nfat Translocation 359mentioning
confidence: 99%
“…This cycle is accompanied by the expression of a series of genes such as those for IL-2, interferon-␥, and the cyclins, which are expressed in a carefully controlled order as the cells pass through the G 0 , G 1 , and S phases (Ajchenbaum et al, 1993;Liu et al, 2004). Indeed, cell cycle activation is in part coordinated by the D-type cyclins, which are rate-limiting and essential for the progression through the G 1 phase of the cycle (Chen et al, 2007). We found that addition of cucurbitacin R affected the cell cycle of stimulated T lymphocytes without exerting any effect on cell viability.…”
Section: Cucurbitacin R Inhibits Nfat Translocation 359mentioning
confidence: 99%